The Effect of Ethanolic Extract of Moringa oleifera Leaves on the Macrophage Count and VEGF Expression on Wistar Rats with Burn Wound - Agnes Stella Valentina; Najatullah; Trilaksana Nugroho; Neni Susilaningsih (HM Publisher, 2022)
Background: One modality type of burn wound therapy is topical silver sulfadiazine. Recently, research about topical herb medicine has grown. Moringa oleifera (MO) is a kind of herb plant that has an anti-inflammation effect and has an influence on angiogenesis, so it tends to faster burn wound healing. This study aimed to prove the effect of ethanolic extract of Moringa oleifera leaves on the macrophage count and VEGF expression in Wistar rats with burn wounds. Methods: The research design that was used is